Could Artificial Downwelling/Upwelling Mitigate Oceanic Deoxygenation in Western Subarctic North Pacific? - Xiao, Canbo; Fan, Wei; Chen, Ying; Zhang, Yao; Tang, Kai; Jiao, Nianzhi (Frontiers in Marine Science, 2021)
Subpolar gyre regions such as the Western Subarctic North Pacific (WSNP) contain sluggish, low-oxygen water and are threatened by loss of oxygen (deoxygenation). Our simulations under RCP 8.5 emission scenario suggest that installing pipes to induce artificial downwelling and upwelling (AD and AU) provides short-term solutions to combat deoxygenation in the WSNP. With no engineering, the WSNP's subsurface oxygen decreases by 30-100 mmol/m^3 by the year 2100. Continuous implementation of AD and AU instead counters this declining trend, and AD is more effective than AU. The oxygenation effect is primarily a consequence of how the two engineering schemes vertically redistribute oxygen via physical processes. AD directly improves oxygen at depth via advecting surface water toward the ocean interior and subsequent enhanced pycnocline mixing, and AU does so via generating compensatory downwelling outside of the pipes. Both schemes take near 40 years to complete the oxygenation. After that, oxygen reaches a new equilibrium state in the WSNP with no further improvement by the engineering. AD and AU both strongly increase primary production surrounding the deployment sites, but lead only to weak enhancement of aerobic respiration in subsurface water and thus a minor impact on the oxygenation. Other unwanted environmental side effects are negligible compared to those caused by rapid climate change within this century, including outgassing of carbon dioxide, pH decrease, and precipitation reduction.